The Association between Negative and Dysexecutive Syndromes in Schizophrenia: A Cross-Cultural Study - H. Ihara; G. E. Berrios; P. J. McKenna (Behavioural Neurology)
This paper examined the relationship between the ‘negative syndrome’ (NS) and the neuropsychological ‘dysexecutive syndrome’ (DES) in schizophrenia. The study also examined whether any relationship that exists between the NS and the DES holds equally for British and Japanese subjects. We compared 26 Japanese with 17 British schizophrenic patients, divided into ‘mild’ and ‘severe’ NS groups, on the basis of performance on neuropsychological tests, including the ‘Behavioural Assessment of Dysexecutive Syndrome’ (BADS). We found that patients with severe NS showed more everyday executive deficits than those with mild NS. The severity of NS was correlated with executive competence. The association between NS and the BADS performance was closer than that between NS and other conventional executive measures. These findings were not influenced by cultural differences between Japanese and British subjects, and, hence, suggested the existence of culture-neutral neurobehavioural processes.